2017
DOI: 10.1111/jai.13515
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of Allocreadium isoporum (Digenea: Allocreadiidae) in three endemic species of cyprinids (Capoeta spp.) in Turkey, in relation to season, host size and sex

Abstract: Three species of cyprinids, i.e., Capoeta antalyensis (n = 112), C. caelestis (n = 99) and C. angorae (n = 178) were collected from the Anatolian Region of Turkey to carry out this investigation. A total of 389 specimens of Capoeta were examined for Allocreadium isoporum infections throughout the four different seasons of 2012. The prevalence and mean intensity of infection of A. isoporum was investigated in relation to the host species, the seasons across the year, host size, and sex. Two-hundred and twenty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Another interesting finding was found in Jeddah where no female fish showed any infestation as opposed to male that showed infestation with only parasitic crustacea (Isopoda and Copepoda). Our findings are different to Khalil [20], Barse [5], Adou et al [21] and Aydogdu et al [22] who found no definite difference in the prevalence and intensity of parasitic infestation according to fish sex.…”
Section: Discussioncontrasting
confidence: 99%
“…Another interesting finding was found in Jeddah where no female fish showed any infestation as opposed to male that showed infestation with only parasitic crustacea (Isopoda and Copepoda). Our findings are different to Khalil [20], Barse [5], Adou et al [21] and Aydogdu et al [22] who found no definite difference in the prevalence and intensity of parasitic infestation according to fish sex.…”
Section: Discussioncontrasting
confidence: 99%
“…Generally, the differentiation of the species was based on a combination of external (ventral and oral suckers’ ratio; body length and width; and its ratio to forebody) and internal (cirrus pouch configuration; uterine extension in hindbody; egg size; disposition of anterior border of vitellarium; esophagus length) features. Based on detailed morphological assessment of found trematodes, we concluded that these worms are significantly different from other Allocreadium spp., in particular A. isoporum from Europe (Looss 1894; Slusarski 1958), but with notable similarity to A. isoporum reported from Turkey (Aydoğdu et al 2018).…”
Section: Discussionmentioning
confidence: 86%
“…and the Turkish A. isoporum (Aydogdu et al . 2018) morphologically diverge in relation to true European A. isoporum in having the vitellarium reaching the mid-level of ventral sucker length vs. the vitellarium not reaching the ventral sucker.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation